Noncontact evaluation of autonomic nervous system activity during exercise by using video analysis - Fumimoto, Kanaru; Okada, Shima; Tsuji, Ryohei; Sakaue, Yusuke; Shiozawa, Naruhiro; Jeong, Hieyong; Makikawa, Masaaki (Frontiers in Digital Health, 2025)
IntroductionAutonomic nervous system activity (ANSA) plays a crucial role in the physical condition experienced during exercise and prolonged physical activity. In other words, ANSA is related to exercise performance and physical condition. Therefore, it is important to continuously monitor ANSA during high-intensity and sustained exercise. To this end, an uncomplicated and noncontact measurement system is preferable. Hence, in this study, we propose a method for the noncontact measurement of capillary contraction and dilation state, representative of ANSA, using a common commercial camera.MethodsSpecifically, we focused on alterations in the green value of facial video images, from which we derived the green-to-blue (G/B) ratio as an indicator of blood vessel dilation and contraction, and to facilitate assessment of their activity. We performed a validation experiment involving exercise tasks using an ergometer in 10 healthy adults (23 ± 1.6 years old). The G/B ratio shows the state of contraction and expansion of facial capillaries, and it was evaluated using heart rate as ground truth data of the fluctuation of autonomic nerve activity.ResultsWe observed an increase in heart rate with decreased G/B ratio during exercise in all subjects. Postexercise, the heart rate decreased but the G/B ratio increased.DiscussionDuring exercise, characterized by dominant sympathetic NSA, the G/B ratio decreased, and recovered after exercise when parasympathetic NSA was dominant. In this way, noncontact evaluation of ASNA was achieved by using the G/B ratio. In the future, this measurement system will be applied to functional tests for heat acclimation.